Challenges and Economic Implications in the Control of Foot and Mouth Disease in Sub-Saharan Africa: Lessons from the Zambian Experience - Y. Sinkala; M. Simuunza; D. U. Pfeiffer; H. M. Munang’andu; M. Mulumba; C. J. Kasanga; J. B. Muma; A. S. Mweene (Veterinary Medicine International)
Foot and mouth disease is one of the world’s most important livestock diseases for trade. FMD infections are complex in nature and there are many epidemiological factors needing clarification. Key questions relate to the control challenges and economic impact of the disease for resource-poor FMD endemic countries like Zambia. A review of the control challenges and economic impact of FMD outbreaks in Zambia was made. Information was collected from peer-reviewed journals articles, conference proceedings, unpublished scientific reports, and personal communication with scientists and personal field experiences. The challenges of controlling FMD using mainly vaccination and movement control are discussed. Impacts include losses in income of over US$ 1.6 billion from exports of beef and sable antelopes and an annual cost of over US$ 2.7 million on preventive measures. Further impacts included unquantified losses in production and low investment in agriculture resulting in slow economic growth. FMD persistence may be a result of inadequate epidemiological understanding of the disease and ineffectiveness of the control measures that are being applied. The identified gaps may be considered in the annual appraisal of the FMD national control strategy in order to advance on the progressive control pathway.